När de som vet köper: Marknadens reaktion på insynshandel - Brodin,Marcus; Dolk Persson,Sebastian; Edlund,Carl (2025)
Title: When Those Who Know Buy: The market’s reaction to insider trading Seminar date: 2025-06-05 Course: FEKH89, Bachelor Degree Project in Financial Management, Undergraduate Level, 15 ECTS-Credits Authors: Marcus Brodin, Sebastian Dolk Persson, Carl Edlund Advisor: Maria Gårdängen Key words: Insider trading; Abnormal return; Event study; Position; Transaction size Research questions: How does the market react to insider trading in OMXS30 companies, and how is this reaction influenced by the insider's position and the size of the transaction? Purpose: The purpose of this thesis is to examine how the market reacts to insider trading in companies listed on the OMXS30 index. Furthermore, the study aims to investigate whether there is a significant difference in market reactions depending on the insider’s position and the size of the respective acquisitions. Methodology: The thesis adopts a deductive approach and is quantitative in nature. An event study has been conducted, and a multiple linear regression has been applied using data from Finansinspektionen and Bloomberg. Cumulative abnormal return has been calculated using the market model. Theoretical perspectives: The theoretical framework is based on the efficient market hypothesis, signaling theory and the volume critique. Results: The market reacts positively to insider purchases in OMXS30 companies, particularly around the time of public disclosure. The clearest reaction occurs immediately after the transaction is made public in the shorter event window. Purchases made by CFOs are perceived as more informative than those by other insiders. Neither other positions nor transaction size showed any clear impact on the market reaction. Conclusions: The study shows that the market reacts positively to insider purchases, but that the reaction is short-lived and limited to the days surrounding the disclosure. The results suggest that the market does not respond uniformly to all types of insiders, with purchases by CFOs being perceived as particularly informative. Neither other positions nor transaction size show any significant relationship with the market reaction. This indicates that certain insider trades are viewed as more credible, while others have no observable effect.
Keywords: Insider trading; Abnormal return; Event study; Position; Transaction size